Effect of Antithyroid Therapies on Bone and Body Composition: A Prospective, Randomized, Clinical Study Comparing Antithyroid Drugs with Radioiodine Therapy - Kansara, Shekhar (Indian J Endocrinol Metab, 2017)
BACKGROUND: Thyrotoxicosis is associated with loss of body weight and bone mineral content (BMC). Antithyroid drugs (ATD) and radioiodine therapy (RIT) are the common options for the management of thyrotoxicosis. We evaluated the effect of ATD and RIT on BMC and body composition. MATERIALS AND METHODS: In this prospective study, we randomized 60 patients of thyrotoxicosis (20–50 years, treatment naïve, males) to receive either ATD (Group 1) using carbimazole or RIT (Group 2). We excluded patients with significant ophthalmopathy and thyroid malignancy. The patients were followed serially for 1 year. Body composition was analyzed using the bioimpedance method and BMC by dual-energy X-ray absorptiometry technique. The data were analyzed using appropriate statistical measures. RESULTS: The patients had a mean age of 33 ± 4.2 years and mean symptoms duration of 8.2 ± 2.7 months before the diagnosis. A total of 51 patients had Graves' disease, and the remaining 9 had toxic multinodular goiter. BMC at lumbar spine and femoral neck improved with both the therapies similarly at the end of 1 year. The body weight, protein, and fat content also increased after 1 year of observation similar between the two groups. None of the observed parameters showed a difference with regard to the mode of ATD. CONCLUSION: ATD and RIT have comparable effects on the bone and body composition in the management of thyrotoxicosis. Further long-term studies are needed to confirm the observed findings.